Cloud Computing and API Integration in Banking: A Transformative Framework for Digital Innovation and Operational Excellence - Dorai Surendar Chittoor, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the transformative impact of cloud computing and API integration on the banking industry, focusing on their combined role in driving digital innovation and operational efficiency. The article investigates how financial institutions leverage cloud platforms to achieve scalability, cost optimization, and enhanced data management capabilities while utilizing APIs to create open banking ecosystems and enable embedded finance solutions. Through a mixed-method analysis combining case studies and qualitative assessments, this article demonstrates how the convergence of cloud technologies and APIs facilitates rapid service deployment, strengthens security frameworks, and enables advanced analytics capabilities in banking operations. The findings reveal significant opportunities for banks in areas such as multi-cloud adoption, blockchain integration, and IoT banking while highlighting critical regulatory compliance challenges and technical complexity. This article contributes to the growing body of literature on digital transformation in financial services by providing a comprehensive framework for understanding the strategic implications of cloud-API integration and offering insights for banking executives navigating technological innovation. The article concludes by identifying key success factors and proposing strategic recommendations for financial institutions pursuing cloud-API transformation initiatives.
Keywords: Cloud Computing; Open Banking APIs; Digital Transformation; Financial Technology; Banking Innovation